Carbonic anhydrase IV inhibits colon cancer development by inhibiting the Wnt signalling pathway through targeting the WTAP–WT1–TBL1 axis. Issue 9 (12th June 2015) - Zhang, Jingwan; Tsoi, Ho; Li, Xiaoxing; Wang, Hua; Gao, Jing; Wang, Kunning; Go, Minnie YY; Ng, Siew C; Chan, Francis KL; Sung, Joseph JY; Yu, Jun
Abstract : Objective: We found that carbonic anhydrase IV (CA4), a member of the carbonic anhydrases, is silenced in colorectal cancer (CRC). We analysed its epigenetic inactivation, biological effects and prognostic significance in CRC. Design: The biological functions of CA4 were determined by in vitro and in vivo tumorigenicity assays. The CA4 co-operator was identified by immunoprecipitation and mass spectrometry. CA4 downstream effectors and signalling pathways were elucidated by promoter luciferase assay, electrophoretic mobility shift assay and chromatin immunoprecipitation. The clinical impact of CA4 was assessed in 115 patients with CRC. Results: CA4 was silenced in all nine CRC cell lines and 92.6% of CRC tumours. The promoter hypermethylation contributed to the inactivation of CA4, and it was detected in 75.7% of the patients with CRC. After a median follow-up of 49.3 months, multivariate analysis showed that the patients with CA4 hypermethylation had a recurrence of Stage II/III CRC. The re-expression of CA4 inhibited cell proliferation, induced apoptosis and cell cycle arrest in the G1 phase. CA4 inhibited the activity of the Wnt signalling pathway and mediated the degradation of β-catenin . CA4 interacted with Wilms' tumour 1-associating protein (WTAP) and induced WTAP protein degradation through polyubiquitination. Moreover, CA4 promoted the transcriptional activity of Wilms' tumour 1 (WT1), an antagonist of the Wnt pathway, which resulted in the induction of transducin β-like protein 1 ( TBL1 ) and the degradation of β-catenin. Conclusions: CA4 is a novel tumour suppressor in CRC through the inhibition of the Wnt signalling pathway by targeting the WTAP–WT1–TBL1 axis. CA4 methylation may serve as an independent biomarker for the recurrence of CRC.